Evolución del sistema financiero privado en términos de solvencia y patrimonio técnico en el contexto del covid 19. - Sanchez Chavez, Astrid Carolina (My University, 2022)
The financial system is the set of components that regulate, allow and integrate the different means to maintain liquidity, purchasing power and circulating capital for both individuals and society; always been in constant change according to global trends. The general objective is to analyze the evolution of the Ecuadorian private financial system in the context of COVID 19 through bibliographic research to describe the changes in terms of technical equity and solvency. A descriptive methodology is applied based on the global environment, effects, social reality and implications as a result of the pandemic to settle criteria on its impact at the socioeconomic level, in relation to the response of banks and financial institutions in the national context; in the results it is found that on a scale the world banks distributed capital to micro-enterprises, encouraged the financing of projects, lowered interest rates, relieved debts to the population and implemented programs to alleviate the social burden in the countries, instead in Ecuador had the opposite effect, debts were not forgiven or interest was lowered, only a longer-term renegotiation was made and new credit barriers were placed; Due to the loss of solvency in the sector, private banking entities protected their assets, did not forgive debt or injected liquidity into the market; Instead, they reduced their portfolio to solidify their operations and increased their capital margin to increase their long-term solvency.
El sistema financiero es el conjunto de componentes que regulan, permiten e integran los diferentes medios para mantener liquidez, capacidad adquisitiva y capital circulante tanto para las personas como la sociedad; estando siempre en constante cambio acorde a las tendencias globales. El objetivo general es analizar la evolución del sistema financiero privado ecuatoriano en el contexto del COVID 19 mediante una investigación bibliográfica para describir los cambios en términos de patrimonio técnico y solvencia. Se aplica una metodología descriptiva partiendo del entorno global, efectos, realidad social e implicaciones a raíz de la pandemia para dirimir criterios sobre su impacto a nivel socioeconómico, en relación a la respuesta de lo bancos e instituciones financieras en el contexto nacional; en los resultados se encuentra que a escala mundial los bancos distribuyeron capitales a las micro empresas, incentivaron el financiamiento de proyectos, bajaron tasas de interés, alivio de deudas a la población e implementaron programas para aliviar la carga social en los países, en cambio en el Ecuador se tuvo el efecto contrario, no se perdonó deudas ni bajaron intereses solo se renegocio a mayor plazo y colocó nuevas barreras crediticias; debido a la pérdida de solvencia en el medio las entidades bancarias privadas protegieron su patrimonio, no condonaron deuda o inyectar liquidez al mercado; en su lugar disminuyeron cartera para dar solidez a sus operaciones e incrementaron margen de respaldo en su capital para aumentar su solvencia a largo plazo.
Keywords: EVOLUCIÓN; SISTEMA; FINANZAS; COVID 19